18F-FDG PET/CT Findings of Ovarian Mesothelioma: A Case Study. (November 2019) - Sun, Rui; Chen, Yue; Huang, Zhanwen
Abstract : Abstract: Ovarian mesothelioma is a rare and aggressive tumor. Early diagnosis of the disease is difficult, delaying effective treatment. Here we report a 50-year-old woman who was referred for an 18 F-FDG PET/CT imaging to assess her newly detected left ovarian mass. The images not only demonstrated a hypermetabolic mass in the left ovary, but also several hepatic low densities with increased FDG uptake, which suggested ovarian malignancy with hepatic metastases. Mesothelioma was diagnosed histopathologically following the biopsy. Our case demonstrates PET/CT findings observed in ovarian mesothelioma.